1989
DOI: 10.1128/jcm.27.12.2849-2850.1989
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the occurrence of the same strain of Campylobacter pylori in the stomach and dental plaque

Abstract: Restriction endonuclease analysis with HindIII, HaeMI, and BglII endonucleases of DNA extracted from each of eight colonies of Campylobacter pylori subcultured from a stomach biopsy and from each of eight colonies subcultured from dental plaque of the same patient indicated that at least three strains were present in the dental plaque but only one strain was present in the biopsy. One of the dental strains had restriction patterns indistinguishable from those of the biopsy isolate, providing evidence that both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(25 citation statements)
references
References 3 publications
0
25
0
Order By: Relevance
“…The bars show the mean OD at 405 nm from a group of four cats, and the brackets enclose nasopharynx, colonic contents, urethra and vagina have failed. 48 H. pylori has been infrequently isolated from dental plaque 49,50 and saliva of humans. 51 Although H. pylori has been documented by PCR in human faeces and dental plaque [52][53][54][55] and H. mustelae has been isolated from ferret faeces, 56,57 only recently has H. pylori been cultured from human faeces.…”
Section: Discussionmentioning
confidence: 99%
“…The bars show the mean OD at 405 nm from a group of four cats, and the brackets enclose nasopharynx, colonic contents, urethra and vagina have failed. 48 H. pylori has been infrequently isolated from dental plaque 49,50 and saliva of humans. 51 Although H. pylori has been documented by PCR in human faeces and dental plaque [52][53][54][55] and H. mustelae has been isolated from ferret faeces, 56,57 only recently has H. pylori been cultured from human faeces.…”
Section: Discussionmentioning
confidence: 99%
“…Shames et al [63], using a restriction endonuclease analysis of DNA, reported that the same strain of H. pylori was present in stomach and dental plaque.…”
Section: The Mouthmentioning
confidence: 99%
“…Studies (10)(11)(12)(13)(14) have described evidence supporting the role of the oral cavity as a reservoir for H. pylori. Occurrence of the same strain of H. pylori in the stomach and DP has been reported (15). Several studies showed that systemic therapy failed to clear H. pylori from DP, despite its clearance from the stomach (7,16,17).…”
Section: Introductionmentioning
confidence: 98%